‘Sausage finger’ with ‘Rice bodies’ - Guru Prasad Reddy; Divya Narain Upadhyaya; Riddhi Jaiswal; Madhu Mati Goel (Indian Journal of Plastic Surgery)
Although both pulmonary and extrapulmonary tuberculosis (TB) are commonly encountered in developing countries, tenosynovitis is an uncommon presentation of musculoskeletal TB. TB mimics a lot of other conditions and causes diagnostic dilemma in day-to-day practice. We present the case of a 30-year-old male who presented with the complaints of swelling of right index finger which was initially suspected to be giant cell tumour of the flexor tendon sheath but on histological examination turned out to be tuberculous tenosynovitis.